Growth of very low birth weight infants and its association with feeding regimens - Mohammad Faizul Haque Khan; MAK Azad Chowdhury; Md. Mahbubul Hoque; Mohammed Maruf-ul-Quader; Mahfuza Shirin; M Monir Hossain; Rumana Aziz (IMC Journal of Medical Science, 2011)
Clinical care of infants with very low birth weight (weighing<1500 gm at birth) in developing countries can be labour intensive and is often associated with a prolonged stay in hospital. Although several studies have shown the benefits of early discharge from the hospital for premature infants, it is still a common practice to delay discharge of these infants until they reach a weight of 2000 gm or more. The present study was undertaken to test the assumption that very low birth weight (VLBW) infants can attain optimum growth at home and to find its association with feeding regimens. This prospective observational study was conducted at Neonatal Out-patient Department, Dhaka Shishu Hospital over a period of 1 year from January 2010 to December 2010. A total of 92 very low birth weight neonates were enrolled during discahrge in the Neonatal Unit of Dhaka Shisu Hospital. Out of these 92 neonates 16 neonates expired while 7, 4 and 1 neonates dropped out in the first, second and third follow up respectively. The neonates after discharge were fed on three types of feeding regimens at home. The feeding regimens were expressed breast milk (EBM), EBM+ infant formula (mixed feeding) and infant formula only).The outcome variable was growth in terms of increase in weight, length and occiputo-frontal circumference (OFC). The other outcome measures were respiratory tract infection (RTI), diarrhoea and anaemia, visit to physician and readmission to hospital for the morbidities they encountered. The neonates were observed up to three consecutive follow-ups from their date of discharge. The median gestational age at birth was 31 weeks. Approximately 57% of the neonates were admitted within 72 hours of birth with median age at admission being 24 hours. Females were slightly higher (54.3%) than the males (45.7%). The mean weight, length and OFC at admission were 1208 gm 39.8 cm and 28.3 cm respectively. The study demonstrated a steady increase of weight, length and OFC of the infants up to a median age of 6 months with mixed and EBM feeding compared to infant formula group. Regarding RTI, diarhoea and anaemia the breast fed group suffered less frequently than the groups fed with infant formula and EBM+infant formula groups. The frequency of visits to physician and hospital admission were significantly lower in the EBM group than the other two groups. Higher frequency of breast feeding reduced the chance of infection and its severity. Infants discharged below1500 gm grew well with exclusive breast milk.